The Emergence of “Sırf Vilâyeti”: Serbian Migrations to the Territory of Banat by the Mid-16th Century and Their Results - Krstić, Aleksandar (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
Serbian migrations to the area of present-day Banat from the late 14th to the second half of the 16th centuries were primarily driven by Ottoman conquests. Ottoman incursions into southern Hungary after the fall of the Serbian state (1459) caused great demographic losses, which the Hungarian authorities tried to compensate for by organising the mass relocations of the population from northern Serbia to their territory. They also accepted those Serbs who were moving to Hungary on their own and who were willing to enter the military service. This paper analyses the results of these migratory movements until the Ottoman conquest of Banat (1552), with a focus on the area of southern Banat, i.e. the nahiyes of Şemlik (Vršac) and Bođça (Bocşa), on the basis of data provided by the first Ottoman census of the Sanjak of Timişoara from 1554.